Maqashid al-Shariah Implementation and Islamic Economics Industry in Indonesia - Ali Abdurroziq; Naysa Buri; Muhammad Arief; Muhamad Taqi (SMART Insight, 2022)
This research focuses on the application of Maqasid al-Syariah to the principles of Islamic economics in Indonesia. It explores the extent to which these concepts are applied in Islamic economic practices in Indonesia. This study used a qualitative research method, using interviews with academics as a data collection method. The findings show that in Islamic banking, hifdzul al-maal is prioritized, because Islamic banking is very closely related to assets, by saving at Islamic banks, our assets are protected from usury, by saving at Islamic banks, our assets are protected from illegitimate transactions. This research ends by recommending further research to discuss more deeply the extent to which Islamic banking is used by Indonesian people, especially Muslims in Indonesia and what factors cause them to remain in conventional commercial banks.